Nanoparticle-macrophage interactions: A balance between clearance and cell-specific targeting - Rattan, Rahul (Bioorg Med Chem, 2017)
The surface properties of nanoparticles (NPs) are a major factor that influences how these nanomaterials interact with biological systems. Interactions between NPs and macrophages of the reticuloendothelial system (RES) can reduce the efficacy of NP diagnostics and therapeutics. Traditionally, to limit NP clearance by the RES system, the NP surface is neutralized with molecules like poly(ethylene glycol) (PEG) which are known to resist protein adsorption and RES clearance. Unfortunately, PEG modification is not without drawbacks including difficulties with the synthesis and associations with immune reactions. To overcome some of these obstacles, we neutralized the NP surface by acetylation and compared this modification to PEGylation for RES clearance and tumor-specific targeting. We found that acetylation was comparable to PEGylation in reducing RES clearance. Additionally, we found that dendrimer acetylation did not impact folic acid (FA)-mediated targeting of tumor cells whereas PEG surface modification reduced the targeting ability of the NP. These results clarify the impact of different NP surface modifications on RES clearance and cell-specific targeting and provide insights into the design of more effective NPs.